Expression of Genes Related to Prostaglandin Synthesis or Signaling in Human Subcutaneous and Omental Adipose Tissue: Depot Differences and Modulation by Adipogenesis - Michaud, Andréanne; Lacroix-Pépin, Nicolas; Pelletier, Mélissa; Daris, Marleen; Biertho, Laurent; Fortier, Michel A.; Tchernof, André (Mediators of Inflammation, 2014)
Objectives. (1) To examine depot-specific PGE2 and PGF2α release and mRNA expression of enzymes or receptors involved in PG synthesis or signaling in human adipose tissues; (2) to identify changes in expression of these transcripts through preadipocyte differentiation; and (3) to examine associations between adipose tissue mRNA expression of these transcripts and adiposity measurements. Methods. Fat samples were obtained surgically in women. PGE2 and PGF2α release by preadipocytes and adipose tissue explants was measured. Expression levels of mRNA coding for enzymes or receptors involved in PG synthesis or signaling were measured by RT-PCR. Results. Cultured preadipocytes and explants from omental fat released more PGE2 and PGF2α than those from the subcutaneous depot and the corresponding transcripts showed consistent depot differences. Following preadipocyte differentiation, expression of PLA2G16 and PTGER3 mRNA was significantly increased whereas COX-1, COX-2, PTGIS, and PTGES mRNA abundance were decreased in both compartments (P≤0.01 for all). Transcripts that were stimulated during adipogenesis were those that correlated best with adiposity measurements. Conclusion. Cells from the omental fat compartment release more PGE2 and PGF2α than those from the subcutaneous depot. Obesity modulates expression of PG-synthesizing enzymes and PG receptors which likely occurs through adipogenesis-induced changes in expression of these transcripts.